Lexical-Historical Graphics of Kohen, Hekal and Melek as Template for Understanding Cultic Roles of Kings during the Monarchy - Olusayo, Bosun Oladejo; Bamidele, Olalekan O. (Advances in Social Sciences Research Journal, 2015)
No Abstract